Ewing′s sarcoma of the maxilla - Vikas Prasad B; Ahmed Mujib B; Bastian T; David Tauro P (Indian Journal of Dental Research, 2008)
Ewing′s sarcoma is an uncommon malignancy that occurs usually in childhood. In most reported cases, the occurrence of this tumor is more in the mandible than the maxilla. A case of Ewing′s sarcoma of the maxilla together with its associated structures is presented and discussed with complete clinical, radiographic, and histological evaluation. Although the prognosis remains poor, an increased rate of survival is now associated with early diagnosis and combined therapy.